If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2f + -5 = 23 Reorder the terms: -5 + 2f = 23 Solving -5 + 2f = 23 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2f = 23 + 5 Combine like terms: -5 + 5 = 0 0 + 2f = 23 + 5 2f = 23 + 5 Combine like terms: 23 + 5 = 28 2f = 28 Divide each side by '2'. f = 14 Simplifying f = 14
| (x-2)(x-7)+k=0 | | 6a^2+11ad-35d^2= | | 8=3h+2 | | 17x+6=46+x | | 9x-43=-54 | | 4(3/2) | | -4+(-6)+17= | | (x+2)(x+7)+k=0 | | y^2/y^8 | | K(x+2)(x+7)=0 | | 3x^2+6x+3y^2=0 | | K(x-2)(x-7)=0 | | -6=u-(-6) | | 4x+5(0)=11 | | 4.6q-3.1-5.1q=-1.5q-2.5 | | 3x-25=10 | | (5x^2)-10x+2=0 | | 5=5m-23+2n | | 2x-(x/2)+((x+1)/4)=9x | | 6q^2+13qd-63d^2= | | 13/1/2 | | (x-2a)(x-2b)=x^2-2(a^2+b^2) | | -y/8=-24 | | 6x+14=78 | | (x-2)(x-2b)=x^2-2(a^2+b^2) | | 8x^2y^2/9x^4y^8 | | 2q-6=0 | | (3x+5)(4x-3)=0 | | 4n^2-20m+24=0 | | x1/2+5=x1/3+7 | | 3s+12=10 | | 1/3x^2-72=0 |